Scientific Misconduct—Insights From the Work of an Ethics Committee. Issue 4 (October 2018) - Glezerman, Marek; Grossman, Ehud
Scientific misconduct does not only relate to falsifying scientific data or plagiarism but may also include improper handling of authorship. A researcher may be cited as author of a manuscript without having contributed to the scientific work involved, another who has fulfilled the requirements of authorship is omitted or his/her name does not appear in the order, which would have been appropriate. All these may reflect various degrees of dishonesty and improper scientific conduct. There are even more severe cases, in which scientific research is sponsored, conducted, and sometimes even published by employees of vested parties who prefer their involvement not being disclosed, using proxy authors instead. This form of ghost authorship may sometimes amount to felony. As chair of the Ethics Committee (M.G.) and Dean (E.G.), both at the Sackler Medical School, Tel Aviv University, we report on our insights related to authorship and present 2 representative cases.